A Comparative Study with Carvedilol and Ivabradine in Ischaemic Heart Disease Patients with Heart Failure - Hoque, Harisul; Ahmed, Khurshed; Kabir, Mohammad Faisal Ibn; Fatema, Nilufar (University Heart Journal, 2019)
Abstract not available University Heart Journal Vol. 15, No. 2, Jul 2019; 60-62